Exogenous Microorganisms Promote Moss Biocrust Growth by Regulating the Microbial Metabolic Pathway in Artificial Laboratory Cultivation - Tian, Chang; Wang, Heming; Wu, Shufang; Bu, Chongfeng; Bai, Xueqiang; Li, Yahong; Siddique, Kadambot H. M. (Frontiers in Microbiology, 2022)
Moss-dominated biocrusts (moss crusts) are a feasible approach for the ecological restoration of drylands, but difficulty obtaining inoculum severely limits the progress of large-scale field applications. Exogenous microorganisms could improve moss growth and be conducive to moss inoculum propagation. In this study, we investigated the growth-promoting effects and potential mechanisms of exogenous microorganism additives on moss crusts. We used an incubator study to examine the effects of inoculation by heterotrophic microorganisms (Streptomyces pactum, Bacillus megaterium) and autotrophic microorganisms (Chlorella vulgaris, Microcoleus vaginatus) combined with Artemisia sphaerocephala gum on the growth of Bryum argenteum, the dominant moss crusts species in sandy deserts. Amplicon sequencing (16S and 18S rRNA) and PICRUSt2 were used to illustrate the microbial community structure and potential function in the optimal treatment at different developmental stages. Our results showed that exogenous microorganisms significantly promoted moss growth and increased aboveground biomass. After 30 days of cultivation, the Streptomyces pactum (1 g kg–1 substrate) + Chlorella vulgaris (3.33 L m–2) treatment presented optimal moss coverage, height, and density of 97.14%, 28.31 mm, and 2.28 g cm–2, respectively. The best-performing treatment had a higher relative abundance of Streptophyta—involved in moss growth—than the control. The control had significantly higher soil organic carbon than the best-performing treatment on day 30. Exogenous microorganisms improved eukaryotic community diversity and richness and may enhance soil microbial functional and metabolic diversity, such as growth and reproduction, carbon fixation, and cellulose and lignin decomposition, based on functional predictions. In summary, we identified the growth-promoting mechanisms of exogenous additives, providing a valuable reference for optimizing propagation technology for moss inoculum.